Funkcijski test roke po Jebsenu - Zupančič, Polonca (Medicinski razgledi, 2000)
The Jebsen hand function test is one of several tests available for hand function. The Slovene version of the test is based on its original British version. The Jebsen hand function test consists of nine subtests that are representative of a wide variety of hand functions: writing, maze drawing, turning cards over, manipulation of small objects, stacking checkers, simulated cating, nut and bolt assembly, manipulating large light objects and manipulating large heavy objects. The sample included the results for 212 volunteers without disabilities. Norms were determined. Data are presented forhand dominance (nondominant/dominant), sex and subtest. A comparison of theSlovene and British versions of the test was also made. It was established that the time required to perform each subtest increases with age. However, there were no significant differences between males and females or between theSlovene and British versions.
Keywords: Hand; roka; Physical examination; motorične sposobnosti; Occupational therapy; delovna terapija; fizikalni pregled; Writing; funkcija; Manipulation, orthopedic; Sex factors; Age factors; diagnostika